Effects of human capital management on the performance of Regional Education Directorate, Kumasi-Ashanti Region - Korantemaa Nsowah, Eunice (2015)
A thesis submitted to the Department of Human Resource and Organisational Development, Kwame Nkrumah University of Science and Technology in Partial Fulfilment of the Requirements for the Award Of MASTER OF BUSINESS ADMINISTRATION (MBA) HUMAN RESOURCE MANAGEMENT–OPTION.